2022
DOI: 10.3389/fimmu.2022.1055304
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of anoikis-related long non-coding RNA immune infiltration in patients with bladder cancer and immunotherapy

Abstract: BackgroundAnoikis is a form of programmed cell death or programmed cell death(PCD) for short. Studies suggest that anoikis involves in the decisive steps of tumor progression and cancer cell metastasis and spread, but what part it plays in bladder cancer remains unclear. We sought to screen for anoikis-correlated long non-coding RNA (lncRNA) so that we can build a risk model to understand its ability to predict bladder cancer prognosis and the immune landscape.MethodsWe screened seven anoikis-related lncRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…7 B). Remarkably, these findings aligned with a previous study to some extent [ 6 ], providing additional support for the significance and applicability of the gene signature in influencing medication decisions for BCa patients. Consequently, our gene signature held valuable potential for guiding the selection of chemotherapy and targeted agents for BCa patients.…”
Section: Resultssupporting
confidence: 88%
“…7 B). Remarkably, these findings aligned with a previous study to some extent [ 6 ], providing additional support for the significance and applicability of the gene signature in influencing medication decisions for BCa patients. Consequently, our gene signature held valuable potential for guiding the selection of chemotherapy and targeted agents for BCa patients.…”
Section: Resultssupporting
confidence: 88%
“…For instance, KEYNOTE-001 showed that patients with more CD8+ T cell infiltration responded better to pembrolizumab than those with less infiltration [27]. Moreover, some studies reported that lncRNA could influence the infiltration level of tumor-infiltrating immune cells [28,29]. Therefore, a currently acknowledged method, CIBERSORT, was utilized to evaluate the association between LINC01614 expression and tumor-infiltrating immune cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…These models demonstrated remarkable predictive performance and were successfully implemented as a means of stratifying patients for personalised treatment. Additionally, Sun et al uncovered potential associations between anoikis-related lncRNAs and bladder cancer [21]. Similarly, the process of anoikis is also known to play a crucial role in the metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%